A hybrid simulation model of passenger emergency evacuation under disruption scenarios: A case study of a large transfer railway station. Issue 3 (2nd July 2020) - Hassannayebi, Erfan; Memarpour, Mehrdad; Mardani, Soheil; Shakibayifar, Masoud; Bakhshayeshi, Iman; Espahbod, Shervin
ABSTRACT: The problem of managing effective pedestrian evacuation during disruptions is a significant challenge because of the complexity and randomness of the passenger flow dynamics as well as the difficulty in predicting the responsive behaviour of the passengers. In this study, a hybrid agent-based and discrete-event simulation model of passenger flow is designed and implemented to assess the service level performance and the crowdedness ratio in a transfer metro station. This study investigates the statistical significance of the results obtained by the design alternatives and the safety analysis of a multiple-level transfer station through a real-world case study. The simulation model is designed to test various disruption scenarios, including train failure in the tunnel, as well as fire at the station gallery of a crowded metro station. The simulation result shows that the evacuation time can be decreased by 19.5%, compared with the basic design layout.